Microwave Combustion for Modification of Transition Metal Oxides. (4th September 2016) - Wan, Jun; Yao, Xu; Gao, Xiang; Xiao, Xu; Li, Tianqi; Wu, Jiabin; Sun, Wanmei; Hu, Zhimi; Yu, Huimin; Huang, Liang; Liu, Meilin; Zhou, Jun
Abstract : The introduction of oxygen vacancy for transition metal oxide is an effective method to tune their conductivity. Here, microwave combustion method is used to quickly synthesize reduced metal oxides and graphene hybrid composite in several minutes. Among these as‐synthesized composites, the reduced orthorhombic Nb2 O5 and graphene oxide (rNb2 O5 /rGO) composite demonstrates great electrochemical performance with a reversible specific capacity of 726.2 C g −1 at 2 mV s −1 in organic electrolyte as well as a good capacity retention of 87% after 3000 cycles at 10 A g −1 . It is believed that this strategy can be a common route to quickly produce oxygen vacancy in oxides and satisfy much more application requirements even for the possibility of industrialization. Abstract : A fast and facile method is reported to introduce oxygen vacancies for various metal oxides through microwave combustion induced carbon reduction method. This provides a common route to quickly produce oxygen vacancies in oxides and satisfies the requirements for a variety of applications.